Perubahan Perilaku Petani Akibat Adanya Keberadaan dan Peran PPL dalam Usahatani Padi Sawah di Desa Makmur Jaya Kecamatan Betara Kabupaten Tanjung Jabung Barat - Bimo Bagus Saputro; Asmaida Asmaida; Rizki Gemala Busyra (Universitas Batanghari Jambi, 2019)
Desa Makmur Jaya is located in Betara District, Tanjung Jabung Barat Regency and this village is one of the village that has potential in agriculture, in 2017 this village is a land area of 250 hectares wich was used for lowland rice farming with production reaching 315 tons and productivity of 1,26 tons/hectare. Increasing activities in cultivating rice fields is a form of change that is inseparable from the role and fresence of field agricultural instructors, while also influencing changes in farmer behavior. Besides that prosperous villages also have farmer groups that have been formed from 2006 by PPL.The purpose of the behaviour of rice farmers due to PPL in the study area. Behavioral changes that one to be studied area the behavior of farmers before and after the existence of PPL in the aspects of seedling, the system of growing rice, types of fertilizer used in pest control and rice plants, the ability to overcome problems with rice cuktivation and the ability to form farmer groups. The type of data used is the type of cross section data with the type of ordinal measuring scale. The data is source from primary data and sekunder data, the primary data is obtained from the regionsl office directly through the questionnaire while the secondary data is taken from the relevant agencies. The methods used is survey method. In this case the sample is farmers who cultivate paddy field before 2006 to 2018. Data about respondents is a promising data source with data collection techniquws by observation, intervies and referring to the topic and tittle of the research proportional random sampling techniqus of sampling with 50 RTP samples.Data from research result are abstracted, tabulated and the average frequency is calculated and then presented for qualitative data, score is given to find out changes in farmer behavior before and after the presence of PPL, namely by adding up all the scores from the farmers sample then continuing to divide each aspect with two categories, namely the inadeguate category and the able category then analyzed using then wilcoxon martch pairs test using a 95% convidents level. The results of he study were using the wilcoxon test, 95% confidence level of a significant level Z with the formula (Siregar, S 2015) yielding a Z count volve of -6,15which compared to the Z table valv of 1,96 was greater than Z counted and taken there was a change in the behavior of the sample farmers in farming paddy rice is covered and after PPL.